The relationship between physical activity and the determinants of cardiovascular health in healthy midlife women - Sawatzky, Jo-Ann V. (2007)
'Background'. Cardiovascular disease (CVD) is the leading cause of death in Canadian women. 'Objective'. The purpose of this study was to explore and describe the relationship between physical activity and the determinants of cardiovascular health in healthy mid-life women. The primary research hypothesis was that physically active women would have a healthier cardiovascular health promotion profile than non-active women. 'Design'. A cross-sectional comparative survey. 'Sample & setting'. A health and fitness facility in Winnipeg, Canada was utilized to access the target population of healthy, mid-life women between 35 and 74 years of age. The 206 women who participated in the study were self-described as healthy, with no previous history of heart disease, cancer, diabetes, or hypertension. 'Conceptual framework'. The Population Health Promotion (PHP) model provided the framework for this research. 'Methods'. The Paffenbarger Physical Activity Questionnaire was used to assess physical activity in the cohort. The demographic data form and the Cardiovascular Health Promotion Profile were derived from the PHP model to encompass the essential components of the determinants of cardiovascular health in women. In addition, blood pressures, resting heart rates, height, weight, waist, and hip measurements were recorded. Data were analyzed with a variety of univariate and multivariate procedures. 'Findings'. Active women were more likely to be members of the facility, younger, and have higher levels of socioeconomic status. Although members' resting heart rates were significantly lower and their perceived health status, as well as their dietary actions and beliefs, were more positive than the non-member cohort, there was minimal support for the hypothesis that membership effects healthier behaviors overall. 'Conclusions'. The evidence suggests that healthy, physically active, mid-life women, especially those who exercise regularly and/or vigorously at least once a week, have a healthier cardiovascular profile than their less active counterparts. In addition, it would appear that membership in a health and fitness facility effects a more active profile. 'Implications'. This research has demonstrated that the PHP model is an appropriate framework to organize existing knowledge and to address research issues related to cardiovascular health. In addition, this study lends support for focusing cardiovascular health promotion strategies on the determinants of cardiovascular health. (Abstract shortened by UMI.)